The Pengaruh komunikasi, motivasi dan kepuasan kerja Terhadap kinerja karyawan: studi empiris hotel harper perintis by aston, makassar - I Gede Arya Pering Arimbawa; Ardhi Goeliling; Tyta Ripal; Arya Bayu Peringga Putra; Abd Rahim Amin (Pusaka: Journal of Tourism, Hospitality, Travel and Business Event, 2023)
The functioning of the parts in the organization depends on the human ability in the organization, especially in communication, motivation, and job satisfaction for the direction of achieving employee performance goals. This study aims to test and prove empirically whether communication, motivation,n and job satisfaction have a positive and significant impact on employee performance. This research is quantitative, popular, ion and sam in research areas e all employees of Hotel Harper Perintis By Aston, Makassar with the current population reachesreachingple. The sampling technique in this case uses a saturated sampling technique. This study was analyzed with SPSS 24 software. The results showed that (1) Communication had a positive and significant influence on the performance of Harper Perintis employees by Aston - Makassar; (2) Motivation positively and significantly influence to employee performance of Harper Perintis by Aston - Makassar and (3) Job satisfaction positively and significantly influence to the performance of Harper Perintis employee by Aston - Makassar.